Immunogenicity and protective efficacy against Salmonella C2-C3 infection in mice immunized with a glycoconjugate of S. Newport Core-O polysaccharide linked to the homologous serovar FliC protein. Issue 6 (3rd June 2019) - Schuster, Ofir; Sears, Khandra T.; Ramachandran, Girish; Fuche, Fabien J.; Curtis, Brittany; Tennant, Sharon M.; Simon, Raphael
ABSTRACT: Nontyphoidal Salmonella (NTS) are important human enteric pathogens globally. Among the different serovars associated with human NTS disease, S . Newport (a serogroup C2 -C3 Salmonella ) accounts for a measurable proportion of cases. However, to date there are no licensed human NTS vaccines. NTS lipopolysaccharide-associated O polysaccharides are virulence factors and protective antigens in animal models. As isolated molecules, bacterial polysaccharides are generally poorly immunogenic, a limitation overcome by conjugation to a protein carrier. We report herein the development of a candidate serogroup C2 -C3 glycoconjugate vaccine based on S . Newport Core-O polysaccharide (COPS) and phase 1 flagellin (FliC). S . Newport COPS and FliC were purified from genetically engineered reagent strains, and conjugated at the polysaccharide reducing end to FliC protein lysines with thioether chemistry. S . Newport COPS:FliC immunization in mice improved anti-polysaccharide immune responses, generated high anti-FliC IgG titers, and mediated robust protection against challenge with both the homologous serovar as well another serogroup C2 -C3 serovar ( S . Muenchen). Analyses of S . Newport COPS:FliC induced sera found that the anti-COPS IgG antibodies were specific for serogroup C2 -C3 lipopolysaccharide, and could promote bactericidal killing by complement and uptake into phagocytes. These preclinical studies establish the protective capacity of serogroup C2 -C3 OPS glycoconjugates, and provide a path forward for the development of a multivalent Salmonella vaccine for humans that includes serogroup C2 -C3 .